Bi-modified 3D BiOBr microsphere with oxygen vacancies for efficient visible-light photocatalytic performance - Hua, Chenghe; Dong, Xiaoli; Wang, Yu; Zheng, Nan; Ma, Hongchao; Zhang, Xiufang (Journal of materials science, 2019)
Flower-like Bi that deposited BiOBr with oxygen vacancies (OVs) has been successfully fabricated via a simple solvothermal method followed by an easy hydrogenated treatment. The characterization results show that three-dimensional (3D) H-1.0Bi@BiOBr microspheres with the diameter about 1.2–1.5 μm were self-assembled by countless two-dimensional (2D) interlaced BiOBr nanosheets. Bi-deposited and oxygen vacancies endowed the H-1.0Bi@BiOBr samples with a dramatically enhanced photocatalytic performance for the degradation of organic pollutants (Rhodamine B and Ofloxacin) and the solar-energy nitrogen fixation. It disclosed that the photocatalytic performance order of the photocatalyst was H 200 -1.0Bi@BiOBr > H 250 -1.0Bi@BiOBr > H 150 -1.0Bi@BiOBr > 1.0Bi@BiOBr > 2.0Bi@BiOBr > 0.5Bi@BiOBr > BiOBr. Particularly, the enhanced photocatalytic activity was ascribed to higher BET specific area, enhanced visible-light absorption, effective photoinduced charge separation and suitable amounts of oxygen vacancies. The H-1.0Bi@BiOBr samples also showed good photochemical stability under repeated visible-light irradiation. This work could shed light on exploring high-photocatalytic-property materials and stimulating the development of OVs-Bi@BiOBr photocatalysts, which had great potential for the solar-energy conversion, environmental purification and organic pollution treatment in water.